Experiential Learning and Social Justice Action: An Experiment in the Scholarship of Teaching and Learning - Glennon, Frederick E. (Teaching theology and religion, 2004)
This essay discusses the process and findings of an experiment on the scholarship of teaching and learning conducted in a religious ethics classroom that utilized an experiential approach to teaching and learning about social justice. The first part lays out the focus of the investigation and the pedagogical principles drawn from experiential learning theory that provided the foundation for the experiment. The second part describes all of the components of the pedagogical strategy used in the experiment, the social justice action project. The third part discusses the qualitative methodology used to gather evidence and the findings drawn from that evidence. What the evidence shows is that an experiential approach to teaching and learning about social justice can be quite effective. The essay concludes with discussions of areas for further study and the implications for the practice of others. (The survey described in this article can be found on the Wabash Center Web site〈http://www.wabashcenter.wabash.edu/journal/glennon.html〉).